PENGARUH MOTIVASI EKSTRINSIK DAN ETOS KERJA TERHADAPPRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PT. SINAR SAMUDRA MARINA PRINGSEWU - Zuriana; AK Yohanson (Bajang Institute, 2022)
The purpose of this study was to gind the effect of extrinsic motivation on the work productivity of the employees at PT. Sinar Samudra Marina Pringsewu, the effect of work ethic on the work productivity of the employees of PT. SinarSamudra Marina Pringsewu, to determine the effect of Extrinsic Motivation andWork Ethic on the work productivity at PT. Sinar Samudra Marina Pringsewu.This study used the quantitative approach with the associative method. The sourceof the data in this study used the primary data. The of data collecting technique inthis study used the field research using the questionnaire technique. Thepopulation of this study was 41 employees with the total sample of 31 employees.The sampling technique in this study used the non-probability sampling, namelythe purposive sampling technique. The instrument requirements test in this studyused the validity test and the reliability test. The data analysis requirements test inthis study used the Normality test, Linearity test and Multi-collinearity test. Thedata analysis method used the Multiple Linear Regression and the hypothesistesting, namely t-test and F test. The result of this study found that extrinsicmotivation had a significant effect on the work productivity of employees in theproduction division of PT. Sinar Samudra Marina Pringsewu, work ethic had asignificant effect on the work productivity of employees in the productiondivision of PT. Sinar Samudra Marina Pringsewu, extrinsic motivation and workethic simultaneously affected the work productivity of the employees in theproduction division of PT. Sinar Samudra Marina Pringsewu